PARTICULAR SOLUTIONS FOR THE GENERALIZED BURGERS-HUXLEY EQUATION BY THE FACTORIZATION METHOD - Taylanov, Nizom; Zokirov, Mamajon; Urazov, Abdixoliq (Физико-технологического образование, 2022)
The article deals with numerical solutions of non-linear partial differential equations, such as the generalized Burgers-Huxley equations, which combine the effects of advection, diffusion, dispersion and non-linear transport. The Burgers-Huxley equation is solved numerically with the use of the factorization method, where a set of special solutions are obtained. It was shown that the factorization method is an efficient method with acceptable accuracy for solving the Burgers-Huxley equation